Upaya Meningkatkan Kualitas Profesionalisme Guru di Masa Pandemi: Pelatihan Penelitian Tindakan - Sriyanto Sriyanto; Yudha Febrianta; Pratik Hari Yuwono; Indri Murniawaty (UM Purwokerto Press, 2022)
The development of the teaching profession during the pandemic declined, because limited interaction and mobility made some teachers reluctant to innovate and be creative in learning. The purpose of this activity is to improve the quality of teacher professionalism through Classroom Action Research training. The methods used are discussions, lectures, and practice of proposal preparation, implementation, and preparation of reports and articles in journals. The result of this service is that the teacher has an understanding of Classroom Action Research after attending the training, can determine problems based on the results of learning reflections, prepare proposals, compile reports and articles in journals.